Minimal Landmarks for Optimal Delete-Free Planning - Haslum, Patrik; Slaney, John; Thiebaux, Sylvie (Proceedings of the International Conference on Automated Planning and Scheduling, 2012)
We present a simple and efficient algorithm to solve delete-free planning problems optimally and calculate the h+ heuristic. The algorithm efficiently computes a minimum-cost hitting set for a complete set of disjunctive action landmarks generated on the fly. Unlike other recent approaches, the landmarks it generates are guaranteed to be set-inclusion minimal. In almost all delete-relaxed IPC domains, this leads to a significant coverage and runtime improvement.